Effect of Starfruit Extract (Averrhoa bilimbi Linn) Using a Combination of Water, Acetone, and Methanol Solvents on Phenolic Content and Antioxidant Capacity - Putri, Dita Audia; Gultom, Milanda Fiorella; Binukajati, Farras Agung; Maulana, Asy Syifa Tickna; Putra, Raihan Permana; Liwanda, Novian; Nurcholis, Waras (Jurnal Jamu Indonesia, 2023)
Starfruit leaves, which belong to the Averrhoa family and contain tannin, saponin, flavonoid, and terpenoid compounds, have been widely used in traditional medicine due to their pharmacological benefits. This study aims to investigate the effect of solvent maceration on the extraction of total phenolics from starfruit leaves and to evaluate their antioxidant activity capacity. The study utilized Wuluh starf leaves obtained from Biofarmaka IPB University, Bogor, Indonesia, in February 023. The total phenolic content (TPC) and antioxidant tests, such as ABTS and FRAP, were influenced by the maceration stage using solvents, such as a combination of water, ethanol, and methanol. The Folin-Ciocalteu reagent and sodium carbonate were used to determine the total phenolic content, and antioxidant tests, such as the reaction with radical cations (ABTS) and the antioxidant reaction with reduction of ferri-trpyridytriazine (FRAP), were used to evaluate the antioxidant activity capacity. The results indicate that extraction with 100% acetone solvent has the FRAP method's highest phenolic content and antioxidant capacity, with 10.6325 mg GAE/g DW and 34.26641 ± 1.82 µmol TE/g DW, respectively. On the other hand, the 50:50 ethanol:acetone solvent had the highest antioxidant activity using the ABTS method, with 100.31 ± 4.80 µmol TE/g DW. The TPC-FRAP standard curve shows a positive correlation with R2 = 0.9388, while the TPC-ABTS and FRAP-ABTS standard curves do not significant correlation with the R2 values of -0.09045 and 0.08038, respectively.